RESPONSES OF MANUFACTURING INDUSTRIES TO POOR INFRASTRUCTURE IN GOMBE METROPOLIS, NORTH EAST NIGERIA, 1963-2013 - UMAR ZUBAIRU; MISBAHU SA’IDU (International Studies Journal)
Beginning from the Industrial Revolution of the 18th and 19th centuries, the nexus between infrastructure and growth of manufacturing has been well established in the literature. As such, poor infrastructure has been identified to have negative effect on industrial development as evident in low capacity utilization and collapse of industries. However, response of manufacturers to infrastructure deficiencies is rarely analyzed in most of the literatures. This gives an impression that manufacturers adopt a lets-wait-and see attitude towards poor infrastructure. It is against this backdrop that this paper interrogates the responses of manufacturing firms to infrastructure decadence within the context of Gombe metropolis in North East Nigeria. Gombe remains a city with overwhelming infrastructure decay which affects its industrialization process.  Thus, there is compelling need to explore how the manufacturers in Gombe face the challenge of infrastructure deficits. A historical method of inquiry based on the use of primary and secondary sources was adopted. The result showed that manufacturers responded to poor public infrastructure through private provisioning, requested public electricity, water supply, factor substitution, output reduction, relocation, and closure. The paper finally contends that collapse of industries due to poor infrastructure in Gombe metropolis was a long and protracted one not sudden or overnight occurrence as often assumed and popularized.